13C and 15N CP/MAS, 1H–15N SCT CP/MAS and FTIR spectroscopy as tools for qualitative detection of the presence of zwitterionic and non‐ionic forms of ansa‐macrolide 3‐formylrifamycin SV and its derivatives in solid state. (6th November 2013) - Przybylski, Piotr; Pyta, Krystian; Klich, Katarzyna; Schilf, Wojciech; Kamieński, Bohdan
<x xml:space="preserve">Abstract</x> 13C, 15N CP/MAS, including 1H–13C and 1H–15N short contact time CP/MAS experiments, and FTIR methods were applied for detailed structural characterization of ansa‐macrolides as 3‐formylrifamycin SV (1) and its derivatives (2–6) in crystal and in powder forms. Although HPLC chromatograms for 2/CH3OH and 2/CH3CCl3 were the same for rifampicin crystals dissolved in respective solvents, the UV–vis data recorded for them were different in 300–375 nm region. Detailed solid state 13C and 15N CP/MAS NMR and FTIR studies revealed that rifampicin (2), in contrast to 3‐formylrifamycin SV (1) and its amino derivatives (3–6), can occur in pure non‐ionic or zwitterionic forms in crystal and in pure these forms or a mixture of them in a powder. Multinuclear CP/MAS and FTIR studies demonstrated also that 3–6 derivatives were present exclusively in pure zwitterionic forms, both in powder and in crystal. On the basis of the solid state NMR and FTIR studies, two conformers of 3‐formylrifamycin SV were detected in powder form due to the different orientations of carbonyl group of amide moiety. The PM6 molecular modeling at the semi‐empirical level of theory, allowed visualization the most energetically favorable non‐ionic and zwitterionic forms of 1–6 antibiotics, strongly stabilized via intramolecular H‐bonds. FTIR studies indicated that the originally adopted forms of these type antibiotics in crystal or in powder are stable in standard laboratory conditions in time. The results presented point to the fact that because of a possible presence of two forms of rifampicin (compound 2), quantification of the content of this antibiotic in relevant pharmaceuticals needs caution. Copyright © 2013 John Wiley & Sons, Ltd.